Novel tetracyclic structures from the synthesis of thiolactone-isatin hybrids - Renate Hazel Hans; Hong Su; Kelly Chibale (Beilstein Journal of Organic Chemistry, 2010)
A simple and straightforward synthetic approach to potential anti-infective thiolactone-isatin hybrids led to the discovery of novel tetracyclic compounds which bear a macrocylic motif containing an unusual bridged amide bond.